METHODOLOGY OF GROUP WORK ORGANISATION FOR STUDENT LEARNING PERFORMANCE IMPROVEMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The article describes the methodology of learning programming for students of various engineering disciplines. The course "Algorithmization and Programming of Solutions" is taught to all first-year students of the Faculty of Computer Science and Information Technology in Riga Technical University and provides the basic knowledge of the principles of computational process algorithmization and software creation technology using Java programming language. There are 8 laboratory assignments in the course, where students have to develop a software programme and 2 group work assignments, where the student has to develop some algorithms to solve a given problem, write a programme, evaluate the speed of developed algorithms and prepare a presentation on the results of their research. The article describes the main principles of efficient student group work organisation that lets to increase their interest and motivate them to participate in the course in a responsible way. This paper is focused on research on how group work influences student learning performance.